China's digital policy: A threat to European business models - Vera Demary; Jürgen Matthes (Institut der deutschen Wirtschaft (IW), 2021)
China is making great strides in regulating digitization. Some aspects are similar to European approaches, but Chinese laws on data security and protection go much further. This may result in a threat to European business models.
Keywords: 330